Comment on ``Strontium clusters: Many-body potential, energetics, and structural transitions'' [J. Chem. Phys. 115, 3640 (2001)] - Doye, J; Calvo, F (American Institute of Physics, 2003)
Parallel tempering simulations for Sr_34 and Sr_61 indicate that, contrary to Wang et al.'s predictions [J. Chem. Phys. 115, 3640 (2001)], there are no solid-solid transitions for these clusters, in which symmetrical polytetrahedral structures become most stable. These results have implications for the structural interpretation of the magic numbers observed experimentally for strontium clusters.